Evaluation of two-dimensional Bruch's membrane opening minimum rim area for glaucoma diagnostics in a large patient cohort - Enders, Philip; Adler, Werner; Kiessling, David; Weber, Vincent; Schaub, Friederike; Hermann, Manuel M.; Dietlein, Thomas; Cursiefen, Claus; Heindl, Ludwig M. (Acta Ophthalmologica, 2019)
Purpose To characterize the two-dimensional parameter Bruch's membrane opening minimum rim area (BMO-MRA) in spectral domain optical coherence tomography (SD-OCT) of the optic nerve head (ONH) compared to minimum rim width (BMO-MRW) and retinal nerve fibre layer (RNFL) thickness in a large patient cohort. Methods Case-control, cross-sectional study of 705 eyes of 445 participants. A total of 449 eyes with glaucoma, 67 eyes with ocular hypertension and 189 healthy controls, underwent SD-OCT and confocal laser scanning tomography (CSLT), visual field testing and clinical examination. Morphometric ONH parameters, visual field function and diagnostic power were compared. Main outcome measures were SD-OCT-derived BMO-MRA, BMO-MRW, RNFL thickness and CSLT-derived rim area (DM-RA). Results Mean ONH area was 2.11 +/- 0.57 mm(2); mean BMO area was 1.89 +/- 0.45 mm(2). Correlation of mean deviation in visual field to morphometric parameters was rho = 0.70, (p < 0.001) for RNFL thickness, rho = 0.68 (p < 0.001) for BMO-MRA, rho = 0.66 (p < 0.001) for BMO-MRW. These correlations were not significantly different (p > 0.05), while DM-RA correlated significantly worse (rho = 0.55; p < 0.001). In receiver operating characteristics, the calculated area under the curve (AUC) and sensitivity at 90% specificity to differentiate glaucoma were 0.87% and 70.1% for BMO-MRA, 0.86% and 68.1% for RNFL thickness, 0.84% and 66.0% for BMO-MRW, 0.82% and 51.3% for DM-RA. Conclusions In a heterogenous clinical cohort of glaucoma patients, all analysed SD-OCT parameters excel DM-RA of CSLT. The two-dimensional parameter BMO-MRA shows comparable levels of diagnostic power to detect glaucoma compared to established parameters BMO-MRW and RNFL thickness. Given higher comparability between ONH sizes, BMO-MRA might become an additional standard tool in SD-OCT imaging for glaucoma.
CRIS-Team WoS Importer:2019-02-21